The economic efficiency of the innovated technology of the primary processing of linseed straw - E. M. Puchkov; A. V. Galkin; I. V. Uschapovsky (Аграрная наука Евро-Северо-Востока, 2018)
In the Russian Federation, linseed is cultivated as an oil crop for seed production then its bast fiber part of a plant does not used due to the lack of processing technology and special equipment. Machinery factory named by Korolev (city Ivanovo) produces domestic equipment for flax primary processing for high price, but which is not adapted to produce fiber from stems of linseed. New low-cost technology and technological equipment for the primary processing of linseed fiber directly on the fields in flax-growing farms without building capital facilities and utilities have been done at the All-Russian Research Institute for Flax Production. This resource-saving technology allows rationally use the biological potential of the crop, to learn new types of production, to create additional jobs in farms and countryside. The calculations of the cost of new technological equipment, volumes of fibrous of raw materials for its processing, cost of linseed fiber producing at all transitions from the field to the final product in comparison with the existing basic technologies and technical means are presented in the article. On the basis of production tests of new equipment and quality characteristics of the obtained linseed fiber, carried out in 2015-2017, the areas of application in textile industry and other sectors of the economy have been recommended - cottoning fibers, nonwoven materials, environmental building insulation, composite materials. The low-cost innovative technology and its using in real economy is available for all categories of farms and fiber processing plants. The advantages of the new technological line compared to the existing baseline AKLV-1-01 (Korolev’s machinery factory) are the following: the processing capacity of raw materials is 1.6 times higher; fiber production with wide rank characteristics, as an average mass-long from 40 to 200 mm, content of shives from 10 to 20%, linear density from 1.5 to 7.0 tex; the power of electric motors was 1.8 times lower (from 65 to 36 kW) , the costs of materials consumption was 1.8 times lower and the cost of equipment decreased from 11.200 to 7.000 thousand rubles. Calculations of economic efficiency of production and the payback of new resource-saving technological equipment confirm the validity of the use of the proposed technology. Additional revenue from the sale of fiber will be more than 2 billion rubles per year, and net profit of more than 500 million rubles. The payback period of the equipment of one production line is less than two years.